TRPV1 receptors augment basal synaptic transmission in CA1 and CA3 pyramidal neurons in epilepsy. (9th February 2016) - Saffarzadeh, F.; Eslamizade, M.J.; Mousavi, S.M.M.; Abraki, S.B.; Hadjighassem, M.R.; Gorji, A.
Graphical abstract: Highlights: TRPV1 expression is up-regulated in the hippocampus in TLE. Basal synaptic transmission is not altered by TRPV1 activation in control slices. TRPV1 activation increased basal synaptic transmission in TLE. TRPV1 inhibition decreased basal synaptic transmission in TLE. Abstract: Temporal lobe epilepsy in human and animals is attributed to alterations in brain function especially hippocampus formation. Changes in synaptic activity might be causally related to the alterations during epileptogenesis. Transient receptor potential vanilloid 1 (TRPV1) as one of the non-selective ion channels has been shown to be involved in synaptic transmission. However, the potential role of TRPV1 receptors in synaptic function in the epileptic brain needs to be elucidated. In the present study, we used quantitative real-time PCR (qRT-PCR), western blotting, and immunohistochemistry to assess hippocampal TRPV1 mRNA expression, protein content, and distribution. Moreover, the effects of pharmacologic activation and inhibition of TRPV1 receptors on the slope of evoked field excitatory postsynaptic potentials (fEPSPs) were analyzed in CA1 and CA3 pyramidal neurons, after 3 months of pilocarpine-induced status epilepticus (SE). SE induced an upregulation of TRPV1 mRNA and protein content in the whole hippocampal extract, as well as its distribution in both CA1 and CA3 regions. Activation and inhibition of TRPV1 receptors (via capsaicin 1 μM and capsazepine 10 μM, respectively) did not influence basal synaptic transmission in CA1 and CA3 regions of control slices, however, capsaicin increased and capsazepine decreased synaptic transmission in both regions in tissues from epileptic animals. Taken together, these findings suggest that a higher expression of TRPV1 in the epileptic condition is accompanied by alterations in basal synaptic transmission.